Z GENERATION BELIEFS AND PRACTICES ON EARLY ENGLISH LANGUAGE DEVELOPMENT FOR THEIR CHILDREN - Yulmiati Yulmiati; Melvina Melvina; Dini Putri (Universitas PGRI Sumatera Barat, 2025)
This study explored the Z Generation's beliefs and practices on early English language development for their children. The research aimed to understand parents' beliefs and practices in supporting early English language development for their children. A qualitative research design was employed, utilizing semi-structured interviews and observations to gather in-depth data from Generation Z as parents with varying educational backgrounds. The findings indicate that Generation Z parents have a positive outlook on early English language learning, recognizing its importance for future educational and career opportunities. They belief that starting English education early is advantageous because children can learn new languages more effectively during their formative years. Parents also emphasized the importance of making the learning process enjoyable and engaging, using strategies aligned with Bruner's modes of learning, enactive, iconic, and symbolic. This study highlights the proactive role Generation Z parents play in their children's early English education and provides insights into effective practices that could benefit educators and policymakers in promoting early language learning.